Production of economic statistics for tourist accommodation services of Belo Horizonte under the flexible geography approach: Produção de estatísticas econômicas para os serviços de acomodação turístico de Belo Horizonte sob abordagem da geografia flexível - César Soares Gonçalves, Caio (Revista de Turismo Contemporâneo, 2020)
This paper aims to produce an experimental economic statistic for the tourist accommodation services for Belo Horizonte under a flexible geography perspective. The starting point is the definition of economic activities in the tourist accommodation concept. The methodology adopted is up-down divided into four steps including filtering processes to accompany the definition, discounts related to obtaining information only for the tourists and procedures for adjustments to the statistics always being compared to the official disclosures and respecting the sum of regions. This analysis revealed an erratic behaviour of the number of establishments in Belo Horizonte across the years and half of the workforce is concentrated in micro and small enterprises. The data from the perspective of the flexible geography allowed to verify where the almost R 86 million indicated by the value added of the tourist accommodations were located in 2015. Keywords: Economic Statistics. Economic Geography. Accommodation Services. Flexible Geography.